John Donne and religious authority in the reformed English church - Sweetnam, Mark S. (Trinity College (Dublin, Ireland). School of English, 2008)
This thesis examines the place of religious authority in the thought of John Donne. The methodology employed is a historically contextualised close reading of Donne's works, with particular focus on the sermons. This reading is informed by a multi-disciplinary approach: historical and theological insights are of particular importance to this study, and allow us to understand Donne in the context of the Reformation. We focus on three principal loci of authority - Scripture, the Church, and the preacher. These areas were chosen, following a reading of Donne's works, because of their evident interest to Donne.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin